Pendampingan Penyusunan Desain Pembelajaran Matematika Berbasis Masalah Menggunakan Prinsip Lesson Study - Tri Candra Wulandari; Nurul Jazilah (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service activity is to assist math teachers in developing active learning designs using Lesson Study principles. This service activity is one of the manifestations of the lecturer-teacher partnership program at school. Through collaborative activities between lecturers and teachers, it will produce products in the form of learning designs which are the result of joint designs between lecturers and teachers using the Lesson Study principle. This service activity is carried out through three forms of activity, namely plan, do and see. In activity plans, teachers and lecturers plan learning activities. This planning activity is carried out together both online and offline. After the plan stage completed, it is followed by do and see activities, there are implementation of learning according to the lesson plan that has been prepared with the model teacher, the teacher who participates in planning, while the lecturer acts as an observer. After the implementation of learning is complete, teachers and lecturers gather to carry out learning reflection by presenting the findings of observations to students. Community service activities using lesson study principles have a positive impact, namely teachers are more open in conveying ideas for preparing lesson plans, students become more active in the learning process in class.